Grief reaction in elderly [Yaşlilikta yas] - (:unkn) unknown (My University, 2006)
We searched related keywords in the Medline (elderly, older adults, geriatric, bereavement, complicated grief) to review the literature on grief reaction of elderly. Getting older brings up losses. As a result of this, grief reaction may occur more often. Normal grief reactions are not much different than the ones given by other age groups. It is reported that depressive symptoms of grief disappear in one or two years. However, grief reaction never ends completely in the elderly. "You can not get rid of, just get used to it" is a commonly used statement. Inhibited grief is seen more often in the elderly. Hypertrophic grief and chronic grief are seen less frequent in the elderly. Medical complications are more frequent in older adults. In older widows, utilization of health services, complaints of somatic symptoms and poor health are more often than the younger ones. Widows experiencing problems with alcohol use in the past display a tendency to increase the amount of alcohol use, cigarette smoking and use of other substances. Mortality is also higher in the grieving elderly. While presence of depression prior to loss, poor psychological and physical health, traumatic losses such as suicide, excessive reaction within days of loss, financial problems and level of stress, more than one loss for widowers are shown as risk factors for major depression, social support is a protective factor. For patients who do not fulfill major depression criteria for DSM-IV, complicated grief criteria was proposed. Besides, principles of treatment of grief reaction were reviewed shortly.
Keywords: Complication; Depression; Elderly; Grief